IMPLEMENTING COLLABORATIVE LEARNING LSLC BASED INSTRUCTION TO ENHANCE TEACHERS` PROFESSIONAL DEVELOPMENT - Yenni Rozimela; Syamwil Syamwil; Nora Fudhla (Fakultas Bahasa dan Seni UNP, 2019)
Even thought collaborative learning is not new in learning English, there are indications that there are still many teachers who do not understand the concept and cannot implement it properly. This article presents the results of the introduction / training of LSLC-based collaborative learning concepts in two Senior High School at Padang for two subjects. The training was conducted in two stages. The first stage was the introduction of concepts. The second stage was training by following the LSLC learning steps: Plan, Do, See. All teachers who participated in the training of the two schools took part in these stages. The results of the implementation indicate that the teacher understood the concepts of collaborative learning and lesson study and they can be considered skillfull enough in implementing collaborative learning.